Direct and Indirect Coupling Entanglements in an Optomechanical Cavity Coupled to a Rydberg Superatom - Dong Yan; Feifan Ren; Lei Huang; Yilongyue Guo; Jing Wang; Kaihui Gu; Hanxiao Zhang (Photonics)
We investigate steady-state entanglement in a hybrid optomechanical cavity coupled to a Rydberg atomic ensemble confined within a single blockade region. The ensemble behaves as one superatom due to the rigid dipole blockade effect. Through optomechanical coupling, three types of bipartite entanglement emerge among the cavity, the Rydberg superatom, and the movable mirror. As the principal quantum number of the Rydberg atoms increases (leading to reduced atomic decay rates), the direct cavity–mirror coupling entanglement is redistributed into direct cavity–superatom coupling entanglement and indirect superatom–mirror coupling entanglement. Counterintuitively, this redistribution culminates in the complete suppression of two direct coupling entanglements, leaving only the indirect coupling entanglement persistent under resonant Stokes sideband conditions. Systematic parameter tuning reveals entanglement transfer pathways and establishes the preference of the superatom–mirror entanglement for specific principal quantum numbers. Furthermore, we demonstrate the thermal robustness of the surviving entanglement up to experimentally accessible temperatures. These findings advance the understanding of quantum entanglement in hybrid quantum systems and suggest applications in quantum information processing.